Biodiesel Production from Castor Oil and Its Application in Diesel Engine - S Ismail; S. A Abu; R Rezaur; H Sinin (Universitas Gadjah Mada, 2014)
In this study, the optimum biodiesel conversion from crude castor oil to castor biodiesel (CB) through transesterification method was investigated. The base catalyzed transesterification under different reactant proportion such as the molar ratio of alcohol to oil and mass ratio of catalyst to oil was studied for optimum production of castor biodiesel. The optimum condition for base catalyzed transesterification of castor oil was determined to be 1:4.5 of oil to methanol ratio and 0.005:1 of potassium hydroxide to oil ratio. The fuel properties of the produced CB such as the calorific value, flash point and density were analyzed and compared to conventional diesel. Diesel engine performance and emission test on different CB blends proved that CB was suitable to be used as diesel blends. CB was also proved to have lower emission compared to conventional diesel.